Determinants of Turnover Intention of Regional Development Bank Employees in Yogyakarta - Marfuah, Marfuah; Luthfiani, Asri Pangesti; Maharani, Yestias (Universitas Muhammadiyah Magelang, 2021)
This study aims to determine the effect of job insecurity, job stress, accounting competence, and role conflict on turnover intention in Regional Development Bank employees in the Province of the Special Region of Yogyakarta. The number of samples used in this study were 45 respondents with purposive sampling method. Data was collected by using the questionnaire method. The results show that job insecurity, job stress, and role conflict have a positive effect on turnover intention, while accounting competence has a negative effect on turnover intention of Regional Development Bank employees in the Special Region of Yogyakarta. The results of this study contribute to the management of the Regional Development Bank in the Province of the Special Region of Yogyakarta as a consideration in managing their human resources. For example, to increase employee loyalty at work, namely by increasing accounting competence, and reducing job insecurity, job stress, and role conflict felt by employees